Permanently transient: Brazilian Dekasseguis in Japan - Beltrão, Kaizô Iwakami (2006)
This article presents the results of part of a project undertaken by the Brazilian Association of Dekasseguis (ABD) regarding this group of Brazilians of Japanese descent who have migrated to Japan. The results are based mainly on answers given to a questionnaire applied in January 2004 to such Brazilian migrants in Japan. One great barrier to the adaptation of these immigrants in Japan is related to their language and customs. Although they have the native Japanese phenotype and reasonably recent Japanese ancestors, they no longer behave like Japanese. This apparent contradiction between being and seeming causes conflicts of adaptation for the migrants and their acceptance by the natives. This conflict of identity already existed in Brazil, but the move to Japan only reinforced their feeling of not belonging to this latter country. It consequently reinforces their Brazilian identity, expressed by the great majority of the individuals who said that the problem they face in Japan is that they “miss Brazil.” The study indicated that most moved to Japan for economic reasons, a fact that explains the higher proportion of men who went alone and the repeated returns in cases of failure in Brazil, especially for those with lower educational levels. The situation of the Dekasseguis, with their constant coming and going between the two countries, frequent internal migrations, job changes and periods of unemployment in Japan (even though sometimes short) typify the Dekassegui movement.